2004
DOI: 10.1093/carcin/bgh135
|View full text |Cite
|
Sign up to set email alerts
|

Induction of orphan nuclear receptor Nur77 gene expression and its role in cadmium-induced apoptosis in lung

Abstract: Cadmium is an environmentally widely dispersed and highly toxic heavy metal that has been classified as a human carcinogen. Using the suppression subtractive hybridization technique, we identified previously 29 cadmium-inducible genes, primarily involved in inflammation, cell survival and apoptosis. Among these genes, we are particularly interested in Nor-1, because this gene belongs to the Nur77 family, which plays a key role in the apoptotic processes of a variety of cells and tissues, including the lung. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…It has been shown that Nur77 is expressed in lung epithelial cells and causes epithelial cell apoptosis following exposure to cadmium. However, the impact of Nur77 in inflammation in epithelial cells was not investigated (37). In the present study, we found that overexpression of Nur77 in airway epithelial cells resulted in a marked reduction in expression levels of diverse proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 62%
“…It has been shown that Nur77 is expressed in lung epithelial cells and causes epithelial cell apoptosis following exposure to cadmium. However, the impact of Nur77 in inflammation in epithelial cells was not investigated (37). In the present study, we found that overexpression of Nur77 in airway epithelial cells resulted in a marked reduction in expression levels of diverse proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 62%
“…Inhibition of Nur77 expression by antisense RNA prevents the apoptotic effect of AHPN/CD437. Rapid induction of Nur77 also occurs in cancer cells after stimulation of apoptosis by a variety of apoptosis-inducing agents, including calcium ionophores, etoposide (VP-16) (Li et al, 2000;Liu, 2002), and phorbol ester (Li et al, 2000;Liu, 2002;Cao et al, 2004a;Lin et al, 2004b), synthetic chenodeoxycholic acid derivatives (Jeong et al, 2003), Di-n-butyltin dichloride (Gennari et al, 2002), histone deacetylase inhibitors (Chinnaiyan et al, 2006), cadmium (Shin et al, 2004), 1,1-bis(3 0 -indolyl)-1-(p-substituted phenyl)-methanes (Chintharlapalli et al, 2005), and induced Nur77 contributes to their apoptotic effects.…”
Section: Nur77 As a Death Factormentioning
confidence: 99%
“…3) Rapid induction of Nur77 has since been observed in cancer cells after stimulation of apoptosis by a variety of apoptosis-inducing agents, including calcium ionophores, etoposide (VP-16), 4,5) phorbol ester, [4][5][6][7] synthetic chenodeoxycholic acid derivatives, 8) di-n-butyltin dichloride, 9) histone deacetylase inhibitors, 10) cadmium, 11) and 1,1-bis(3Ј-indolyl)-1-(p-substituted phenyl)methanes.…”
Section: Notesmentioning
confidence: 99%